Recalling All the Olympians: W. B. Yeats’s “Beautiful Lofty Things,” On the Boiler and the Agenda of National Rebirth - Pietrzak, Wit (Text Matters: A Journal of Literature, Theory and Culture, 2014)
While it has been omitted by numerous critics in their otherwise comprehensive readings of Yeats’s oeuvre, “Beautiful Lofty Things” has been placed among the mythical poems, partly in accordance with Yeats’s own intention; in a letter to his wife, he suggested that “Lapis Lazuli, the poem called ‘To D. W.’ ‘Beautiful Lofty Things,’ ‘Imitated from the Japanese’ & ‘Gyres’ . . . would go well together in a bunch.” The poem has been inscribed in the Yeats canon as registering a series of fleeting epiphanies of the mythical in the mundane. However, “Beautiful Lofty Things,” evocative of a characteristically Yeatsian employment of myth though it certainly is, seems at the same time to fuse Yeats’s quite earthly preoccupations. It is here argued that the poem is organized around a tightly woven matrix of figures that comprise Yeats’s idea of the Irish nation as a “poetical culture.” Thus the position of the lyric in the poet’s oeuvre deserves to be shifted from periphery towards an inner part of his cultural and political ideas of the time. Indeed, the poem can be viewed as one of Yeats’s central late comments on the state of the nation and, significantly, one in which he is able to proffer a humanist strategy for developing a culturally modern state rather than miring his argument in occasionally over-reckless display of abhorrence of modernity.